Composite current collector, pole piece, and preparation method and application thereof

CN122950488APending Publication Date: 2026-10-20BEIJING CHEHEJIA AUTOMOBILE TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610048988.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-01-14
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

然而,相较于电解液,固态电解质往往存在固-固界面接触不良、离子/电子传导网络不连续等问题,导致阻抗升高,进而影响电芯容量发挥、循环等电化学性能

Benefits of technology

将无机固态电解质以阵列的形式分布在集流体的表面,通过垂直于集流体的固态电解质向周围的活性物质进行离子/电子传导,由于固态电解质为阵列排布,通过调整阵列的结构可以在固态电解质和活性物质间形成稳定且连续的离子/电子传导网络,并改善固态电解质固-固界面接触状况,降低阻抗,进而改善电芯的容量发挥、循环等电化学性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This application proposes a composite current collector, an electrode, a method for preparing the same, and its applications. The composite current collector includes a current collector and multiple solid electrolytes: the multiple solid electrolytes are arrayed and distributed in at least a portion of the surface of at least one surface of the current collector, and the solid electrolytes include inorganic solid electrolytes. The composite current collector of this application, by distributing inorganic solid electrolytes in an array on the surface of the current collector, can form a stable and continuous ion / electron conduction network, improve the solid-solid interface contact of the solid electrolytes, reduce impedance, and thus improve the capacity utilization, cycle life, and other electrochemical performance of the battery cell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of secondary battery technology, and in particular to a composite current collector, electrode, preparation method and application thereof. Background Technology

[0002] With the widespread use of rechargeable batteries in passenger vehicles, people are paying increasing attention to their safety performance. Using solid electrolytes instead of liquid electrolytes can effectively improve the intrinsic safety of batteries and enhance their overcharge / crush / puncture safety performance. However, compared to electrolytes, solid electrolytes often have problems such as poor solid-solid interface contact and discontinuous ion / electron conduction networks, leading to increased impedance and thus affecting the cell's capacity utilization, cycle life, and other electrochemical performance.

[0003] To address the aforementioned issues, related technologies have developed electrodes made by directly mixing solid electrolyte materials into electrode active materials to create mixed solid electrolyte electrodes. However, due to the rigid point contact between the solid electrolyte and the electrode active particles, a continuous electron / ion conduction network cannot be formed, resulting in unsatisfactory improvement.

[0004] Therefore, how to effectively improve the solid-solid interface contact condition of solid electrolytes and the continuity of ion / electron conduction networks to reduce impedance and improve the electrochemical performance of the battery cell is an urgent technical problem to be solved. Summary of the Invention

[0005] In view of this, one objective of this application is to provide a composite current collector in which inorganic solid electrolyte is distributed in an array on the surface of the current collector, which can form a stable and continuous ion / electron conduction network, improve the solid-solid interface contact of the solid electrolyte, reduce impedance, and thus improve the capacity utilization, cycle life and other electrochemical performance of the cell.

[0006] Another objective of this application is to provide an electrode sheet.

[0007] Another objective of this application is to provide a method for preparing an electrode sheet.

[0008] Another objective of this application is to provide a battery cell.

[0009] Another object of this application is to provide a secondary battery.

[0010] Another object of this application is to provide an electrical device.

[0011] To achieve the above objectives, the first aspect of this application proposes a composite current collector, comprising: current collector; A plurality of solid electrolytes, wherein the array of the plurality of solid electrolytes is distributed in at least a portion of at least one surface of the current collector, wherein the solid electrolytes include inorganic solid electrolytes.

[0012] The composite current collector described in this application can bring at least the following beneficial effects: Inorganic solid electrolytes are distributed in an array on the surface of the current collector. Ion / electron conduction is carried out to the surrounding active material through the solid electrolyte perpendicular to the current collector. Since the solid electrolyte is arranged in an array, a stable and continuous ion / electron conduction network can be formed between the solid electrolyte and the active material by adjusting the structure of the array. This improves the solid-solid interface contact of the solid electrolyte, reduces impedance, and thus improves the capacity utilization, cycle life and other electrochemical performance of the cell.

[0013] In some implementations, the array distribution may take the form of a dot matrix.

[0014] In some embodiments, the maximum dimension of the solid electrolyte in a first direction is a cm, where a satisfies: 0 < a ≤ 1; the first direction is parallel to the surface of the current collector where the solid electrolyte is located.

[0015] In some implementations, 'a' satisfies: 0.05 < a ≤ 1.

[0016] In some embodiments, the distance between two adjacent solid electrolytes located on the same surface of the current collector is b cm, where b satisfies: 0 < b ≤ 1.

[0017] In some implementations, b satisfies: 0.1 < b ≤ 1.

[0018] In some embodiments, the maximum dimension of the solid electrolyte in the second direction is c μm, where c satisfies: 0 < c ≤ 200; the second direction is the direction perpendicular to the surface of the current collector where the solid electrolyte is located.

[0019] In some embodiments, the inorganic solid electrolyte includes at least one of lithium aluminum titanium phosphate, lithium lanthanum zirconium oxide, lithium lanthanum titanate, aluminum-doped lithium lanthanum zirconium oxide, lithium germanium phosphorus sulfide, lithium phosphorus sulfide chloride, and lithium germanium aluminum phosphate.

[0020] In some embodiments, the current collector includes a positive current collector or a negative current collector.

[0021] A second aspect of this application provides an electrode sheet comprising an electrode material layer and a composite current collector as described in the first aspect of this application; the electrode material layer is disposed on the surface of the current collector on which the plurality of solid electrolytes are disposed.

[0022] The electrode described in this application, in addition to having the beneficial effects of the composite current collector of the first aspect of this application, also has the following beneficial effects: Because a composite current collector with a solid electrolyte is used, the active material of the electrode can be a high-capacity material, such as ultra-high nickel ternary material (positive electrode) or silicon-carbon material (negative electrode). The electrode made of high-capacity active material can significantly improve the energy density of the cell. At the same time, because no electrolyte is used, the safety performance of the cell is effectively improved.

[0023] In some embodiments, the plurality of solid electrolytes penetrate the electrode material layer along the second direction.

[0024] In some embodiments, the outer surface of the electrode material layer in the second direction is flush with the outer surface of the solid electrolyte in the second direction.

[0025] In some embodiments, the mass content of the plurality of solid electrolytes in the electrode is d%, where d satisfies: 1≤d≤15.

[0026] In some embodiments, the electrode material layer includes a positive electrode active material or a negative electrode active material.

[0027] A third aspect of this application discloses a method for preparing an electrode sheet, comprising: The composite current collector is rolled with the material of the electrode material layer; During the rolling process, the roll gap is gradually reduced, and the current collector has at least one surface of the plurality of solid electrolytes facing the electrode material layer.

[0028] The electrode preparation method described in this application, in addition to having the beneficial effects of the composite current collector described in the first aspect and the electrode described in the second aspect, also has the following beneficial effects: By gradually reducing the gap between the rollers during the rolling process, the active material and the composite current collector can be tightly bonded together, increasing the surface contact between the active material and the composite current collector, further improving the solid-solid interface contact of the solid electrolyte, and reducing the impedance.

[0029] The fourth aspect of this application provides a battery cell comprising a positive electrode and a negative electrode, wherein the positive electrode and / or the negative electrode are the electrodes described in the second aspect of this application; or, The positive electrode and / or the negative electrode are prepared by the electrode preparation method described in the third aspect of this application.

[0030] The fifth aspect of this application proposes a secondary battery, comprising the battery cell described in the fourth aspect of this application.

[0031] The sixth aspect of this application provides an electrical device comprising the secondary battery described in the fifth aspect of this application.

[0032] The battery cell, secondary battery, and electrical device described in this application all have at least the beneficial effects of the composite current collector, electrode, and electrode preparation method described in this application.

[0033] Additional aspects and advantages of this application will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of this application. Attached Figure Description

[0034] The above and / or additional aspects and advantages of this application will become apparent and readily understood from the following description of the embodiments taken in conjunction with the accompanying drawings. in: Figure 1 This is a schematic front view of a composite current collector, as shown in an exemplary embodiment of this application.

[0035] Figure 2 This is a top view of a composite current collector, illustrating an exemplary embodiment of this application.

[0036] Figure 3 This is a schematic front view of a composite current collector, as shown in another exemplary embodiment of this application.

[0037] Figure 4 The diagram above shows a top view of a composite current collector, which is another exemplary embodiment of this application.

[0038] Figure 5 This is a schematic cross-sectional view of an electrode structure shown in another exemplary embodiment of this application.

[0039] Figure label: 1-Current collector; 2-Solid electrolyte; 3-Electrode material layer. Detailed Implementation

[0040] The embodiments of this application are described in detail below, with examples of these embodiments illustrated in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to explain this application, and should not be construed as limiting this application.

[0041] In this application, the disclosure of numerical ranges includes all values ​​throughout the range and the disclosure of further subdivisions of the range, including the endpoints and subranges given for these ranges.

[0042] Unless otherwise specified, all raw materials and equipment involved in this application are self-made through commercial means or known methods; and all methods involved are conventional methods unless otherwise specified.

[0043] When the term “and / or” is used in a list containing two or more items, it means that any of the listed items can be used alone or in combination with any one or more of the listed items. For example, the expression “A and / or B” is intended to mean A or B or A and B, that is, A only, B only, or a combination of A and B.

[0044] The inventors discovered that, compared to electrolytes, solid electrolytes often suffer from poor solid-solid interface contact and discontinuous ion / electron conduction networks. To address these issues, the inventors further discovered that uniformly and regularly coating inorganic solid electrolytes in an array onto the current collector surface of an electrode creates a stable and continuous ion / electron conduction network. Compared to traditional electrodes with mixed solid electrolytes, this allows for rapid ion / electron transport, resolving the high impedance problem inherent in solid electrolyte applications and improving the electrochemical performance of the battery cell.

[0045] The following description, with reference to the accompanying drawings, describes an embodiment of a composite current collector, electrode, etc.

[0046] <Composite Current Collector> Figure 1 This is a front view of a composite current collector shown as an exemplary embodiment of this application.

[0047] like Figure 1 As shown, the composite current collector in this embodiment includes a current collector 1 and a plurality of solid electrolytes 2.

[0048] like Figure 1 and Figure 3 As shown, the plurality of solid electrolytes 2 arrays are distributed in at least a portion of at least one surface of the current collector 1, and the solid electrolytes 2 include inorganic solid electrolytes.

[0049] It is understood that, in the embodiments of this application, multiple solid electrolytes can be arrayed on one surface of the current collector (e.g., Figure 1-2 ), or it can be distributed on multiple surfaces (e.g. Figure 3-4 Furthermore, multiple solid electrolytes can be distributed in a portion of the surface of the current collector, or they can be distributed across the entire surface. The array distribution is uniform and regular.

[0050] The composite current collector described in this application can bring at least the following beneficial effects: Inorganic solid electrolytes are distributed in an array on the surface of the current collector. Ion / electron conduction is carried out to the surrounding active material through the solid electrolyte perpendicular to the current collector. Since the solid electrolyte is arranged in an array, a stable and continuous ion / electron conduction network can be formed between the solid electrolyte and the active material by adjusting the structure of the array. This improves the solid-solid interface contact of the solid electrolyte, reduces impedance, and thus improves the capacity utilization, cycle life and other electrochemical performance of the cell.

[0051] It should be noted that in the embodiments of this application, the solid electrolyte cannot be a polymer electrolyte because polymer electrolytes are flexible materials and cannot stably form a three-dimensional array structure. They will deform during the rolling process.

[0052] In some embodiments, the array distribution includes, but is not limited to, a lattice. Using these array configurations, ion / electron conduction can be performed from the solid electrolyte perpendicular to the current collector to the surrounding active material. Because the solid electrolyte is arranged in an array, a stable and continuous ion / electron conduction network can be formed between the solid electrolyte and the active material by adjusting the array structure.

[0053] As an optional example, the array distribution is in the form of a lattice, and more preferably a cylindrical lattice. Compared to other array forms, because the solid electrolyte is arranged in an array, a stable and continuous ion / electron conduction network can be formed between the solid electrolyte and the active material by adjusting the array structure, thereby improving the solid-solid interface contact and reducing impedance.

[0054] In some embodiments, the maximum dimension of the solid electrolyte in the first direction is a cm, where a satisfies: 0 < a ≤ 1; the first direction is parallel to the surface of the current collector where the solid electrolyte is located. When the maximum dimension of the solid electrolyte in the first direction is within the above range, a stable and continuous ion / electron conduction network can be formed between the solid electrolyte and the active material, and the solid-solid interface contact condition of the solid electrolyte can be improved.

[0055] For example, the maximum size of the solid electrolyte in the first direction includes, but is not limited to, 0.05cm, 0.1cm, 0.15cm, 0.2cm, 0.25cm, 0.3cm, 0.35cm, 0.4cm, 0.45cm, 0.5cm, 0.55cm, 0.6cm, 0.65cm, 0.7cm, 0.75cm, 0.8cm, 0.85cm, 0.9cm, or 0.95cm.

[0056] In some implementations, 'a' satisfies: 0.05 < a ≤ 1. The maximum size of the solid electrolyte in the first direction is within this range.

[0057] In some embodiments, the spacing between two adjacent solid electrolytes on the same surface of the current collector is b cm, where b satisfies: 0 < b ≤ 1. A spacing within this range between two adjacent solid electrolytes on the same surface can form a stable and continuous ion / electron conduction network between the solid electrolyte and the active material, and improve the solid-solid interface contact of the solid electrolyte.

[0058] For example, the spacing between two adjacent solid electrolytes on the same surface of the current collector includes, but is not limited to, 0.05cm, 0.1cm, 0.15cm, 0.2cm, 0.25cm, 0.3cm, 0.35cm, 0.4cm, 0.45cm, 0.5cm, 0.55cm, 0.6cm, 0.65cm, 0.7cm, 0.75cm, 0.8cm, 0.85cm, 0.9cm, or 0.95cm.

[0059] In some embodiments, b satisfies: 0.1 < b ≤ 1. The spacing between two adjacent solid electrolytes on the same surface is within this range.

[0060] In some embodiments, the maximum dimension of the solid electrolyte in the second direction is c μm, where c satisfies: 0 < c ≤ 200; the second direction is perpendicular to the current collector surface where the solid electrolyte is located. The maximum dimension of the solid electrolyte in the second direction determines the areal density of the coating. Within this range, the areal density of the active material can be maximized while meeting processing requirements, effectively increasing the capacity of the positive and negative electrode sheets, and thus improving the energy density of the battery cell.

[0061] For example, the maximum size of the solid electrolyte in the second direction includes, but is not limited to, 10μm, 20μm, 30μm, 40μm, 50μm, 60μm, 70μm, 80μm, 90μm, 100μm, 110μm, 120μm, 130μm, 140μm, 150μm, 160μm, 170μm, 180μm or 190μm.

[0062] As an optional example, the solid electrolyte has a maximum size of 200 μm in the second direction. This allows for a better and more efficient increase in the areal density of the active material while meeting processing requirements, effectively improving the capacity of the positive and negative electrode plates, and ultimately increasing the energy density of the battery cell.

[0063] It should be noted that in the embodiments of this application, the shape of the solid electrolyte is not limited. It can be a regular shape such as a cylinder, cuboid, or sphere, or other irregular shapes.

[0064] When the shape is cylindrical or cuboid, the maximum dimensions of the solid electrolyte need to be limited in both the first and second directions. In particular, when the shape is cylindrical, the maximum dimension in the first direction is the diameter of the circular base of the cylinder.

[0065] When the shape is a sphere or similar, it is only necessary to limit the maximum size of the solid electrolyte in the second direction, which is also the diameter of the sphere.

[0066] In some implementations, a and b satisfy the following relationship: .

[0067] The above relationship between a and b can fully utilize the ion transport capability of each solid electrolyte column, ensuring optimal ion / electron transport within a reasonable spatial range and improving the fast charging capability of the battery cell.

[0068] In the embodiments of this application, the number of solid electrolytes 2 is not limited and can be more than two, for example, two to four, including but not limited to two, three, four, etc. In some cases, the specific number can be set according to needs, based on the surface size of the current collector where the solid electrolyte 2 is located, provided that the requirements of a, b, and c above are met.

[0069] In some embodiments, the inorganic solid electrolyte includes, but is not limited to, lithium aluminum titanium phosphate (PET). LATP (London Lanthanum Zirconium Oxide Compound) (abbreviated as LLZO), lithium lanthanum titanate (LZO) LLTO (Lithium Lanthanum Zirconium Oxide), aluminum-doped lithium lanthanum zirconium oxide (LLTO) Al-LLZO (abbreviated as Al-LLZO), lithium germanium phosphorus sulfur compounds ( LGPS), lithium phosphorus sulfur chloride compounds ( LPSCl, lithium aluminum germanium phosphate (LPSCl) At least one of the following: inorganic solid electrolytes (e.g., LAGP). Choosing these materials for inorganic solid electrolytes can accelerate electron / ion transport between the positive and negative electrodes, improving the fast-charging capability of the battery cell, while eliminating the need for electrolytes and enhancing battery safety.

[0070] As an optional example, the inorganic solid electrolyte is lithium aluminum titanium phosphate (lithium titanium phosphate). LATP (London Lanthanum Zirconium Oxide Compound) At least one of (LLZO).

[0071] In some embodiments, the current collector includes a positive current collector or a negative current collector. Choosing a positive or negative current collector can accelerate electron / ion transport between the positive and negative electrodes through the solid electrolyte, thereby improving the fast-charging capability of the battery cell.

[0072] It should be noted that the positive and negative current collectors here refer to any positive and negative current collectors well known in the art that can be used in secondary batteries. For example, the positive current collector can be aluminum foil, carbon-coated aluminum foil, composite aluminum foil composed of aluminum and polymers (e.g., polymer-aluminum, etc.), etc., and aluminum foil is optional; the negative current collector can be copper foil, composite copper foil composed of copper and polymers (e.g., copper-polymer-copper, etc.), etc., and copper foil is optional.

[0073] In the case of composite aluminum foil composed of aluminum and polymers, and composite copper foil composed of copper and polymers, the polymers can be at least one of polyethylene terephthalate (PET), polypropylene (PP), etc.

[0074] It is understandable that when the current collector in the composite current collector is a positive current collector, the composite current collector is used for positive electrode plates such as secondary batteries; when the current collector in the composite current collector is a negative current collector, the composite current collector is used for negative electrode plates such as secondary batteries.

[0075] <Extreme Film> Figure 5 This is a cross-sectional view of an electrode shown for another exemplary embodiment of this application.

[0076] like Figure 5 As shown, the electrode sheet of this application embodiment includes an electrode material layer 3 and a composite current collector as described in this application embodiment; the electrode material layer 3 is disposed on the surface of the current collector 1 on which the plurality of solid electrolytes 2 are disposed.

[0077] The electrode sheet of this application embodiment, in addition to having the beneficial effects of the composite current collector of this application embodiment, also has the following beneficial effects: By employing a composite current collector with a solid electrolyte, the active material of the electrode can be a high-specific-capacity material, such as ultra-high-nickel ternary material (positive electrode) or silicon-carbon material (negative electrode). Electrodes made from high-specific-capacity active materials can significantly improve the energy density of the battery cell. Simultaneously, because no electrolyte is used, the safety performance of the battery cell is effectively improved. In some embodiments, the multiple solid electrolytes penetrate the electrode material layer along the second direction. This arrangement forms a continuous ion / electron transport network in the direction perpendicular to the current collector, ensuring consistent performance of the active material on the upper and lower surfaces of the electrode, thus improving the consistency of the battery cell.

[0078] In some embodiments, the outer surface of the electrode material layer in the second direction is flush with the outer surface of the solid electrolyte in the second direction. This arrangement allows for the formation of a continuous ion / electron transport network in the direction perpendicular to the current collector, ensuring consistent performance of the active materials on the upper and lower surfaces of the electrode and improving the consistency of the battery cell.

[0079] In some embodiments, the mass content of the plurality of solid electrolytes in the electrode is d%, where d satisfies: 1 ≤ d ≤ 15. A lower mass content of the plurality of solid electrolytes in the electrode can increase the content of active material in the electrode and improve the energy density of the battery cell.

[0080] For example, the mass content of the plurality of solid electrolytes in the electrode includes, but is not limited to, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, or 14%.

[0081] Depending on whether the current collector in the composite current collector is a positive current collector or a negative current collector, the composite current collector in this application embodiment can be used for the positive electrode or negative electrode of a secondary battery, etc.

[0082] Therefore, in some embodiments, when the current collector in the composite current collector is a positive current collector, the electrode is a positive electrode; in other embodiments, when the current collector in the composite current collector is a negative current collector, the electrode is a negative electrode.

[0083] Furthermore, in some embodiments, when the current collector in the composite current collector is a positive current collector, the electrode material layer includes a positive active material, which is a compound that enables lithium to be reversibly inserted and extracted, and the electrode sheet is the aforementioned positive electrode sheet; in other embodiments, when the current collector in the composite current collector is a negative current collector, the electrode material layer includes a negative active material, and the electrode sheet is the aforementioned negative electrode sheet.

[0084] For example, the positive electrode active material includes, but is not limited to, at least one of high-specific-capacity materials such as lithium nickel cobalt manganese oxide, lithium spinel manganese oxide, and lithium-rich manganese-based materials. Selecting these materials as the positive electrode active material can improve the charging specific capacity of the battery cell and increase its energy density.

[0085] As an alternative example, lithium nickel cobalt manganese oxide (LCMCO) is used as the positive electrode active material. Compared to other materials, choosing LCMCO as the positive electrode active material allows for higher capacity at a relatively higher voltage platform.

[0086] Optionally, in lithium nickel cobalt manganese oxide: the mass content of nickel is 30-98%, including but not limited to 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90% or 92%; the mass content of cobalt and manganese is independently 1-40%, including but not limited to 5%, 10%, 15%, 20%, 25%, 30% or 35%.

[0087] For example, the negative electrode active material includes, but is not limited to, at least one of graphite, silicon carbide materials, silicon oxides, and mixtures of graphite and silicon. Among these, silicon carbide materials include, but are not limited to, silicon carbide and silicon carbide composite materials (e.g., silicon carbide composite materials with a core-shell structure, where silicon is the core and carbon layers are the coating). Selecting these materials as the negative electrode active material can improve the specific charging capacity of the battery cell and increase its energy density.

[0088] It should be noted that, in the embodiments of this application, when the electrode material layer includes a positive electrode active material, the electrode material layer may further include a positive electrode conductive agent, a positive electrode binder, etc.; when the electrode material layer includes a negative electrode active material, the electrode material layer may further include a negative electrode conductive agent, a negative electrode binder, a negative electrode thickener, etc.

[0089] In the embodiments of this application, there are no restrictions on the specific materials selected for the above-mentioned positive electrode conductive agent, positive electrode binder, negative electrode conductive agent, negative electrode binder, negative electrode thickener, etc. They can be any positive electrode conductive agent, positive electrode binder, negative electrode conductive agent, negative electrode binder, negative electrode thickener, etc. that are well known in the art and can be used in secondary batteries, especially all-solid-state batteries.

[0090] <Preparation Method of Electrode> The electrode preparation method of this application embodiment can be used to prepare the electrode of this application embodiment.

[0091] The method for preparing the electrode sheet according to the embodiments of this application includes: The composite current collector is rolled with the material of the electrode material layer; During the rolling process, the roll gap is gradually reduced, and the current collector has at least one surface of the plurality of solid electrolytes facing the electrode material layer.

[0092] In the embodiments of this application, the solid electrolyte has gaps, and the electrode material can fill the gaps in the solid electrolyte during the rolling process.

[0093] In some embodiments, the rolling process includes multiple successive rolling processes.

[0094] The electrode preparation method of this application embodiment, in addition to having the beneficial effects of the composite current collector and electrode of this application embodiment, also has the following beneficial effects: By gradually reducing the gap between the rollers during the rolling process, the active material and the composite current collector can be tightly bonded together, increasing the surface contact between the active material and the composite current collector, further improving the solid-solid interface contact of the solid electrolyte, and reducing the impedance.

[0095] In some embodiments, the rolling process is hot rolling. Using hot rolling can improve the processing performance of the composite current collector, increase the flexibility of the material, and reduce the frequency of replacement of the composite current collector with a smaller roll gap.

[0096] In some embodiments, the temperature of the roller pressing is 60-90°C, including but not limited to 65°C, 70°C, 75°C, 80°C or 85°C.

[0097] <Battery cell> The battery cell of this application includes a positive electrode and a negative electrode, wherein the positive electrode and / or the negative electrode are the electrodes of the embodiments of this application; or, the positive electrode and / or the negative electrode are electrodes prepared by the electrode preparation method of the embodiments of this application.

[0098] It is understood that in the battery components of this application embodiment, the positive electrode and the negative electrode may individually contain the composite current collector of this application embodiment, or they may simultaneously contain the composite current collector of this application embodiment.

[0099] In some embodiments, the battery cell further includes a solid electrolyte membrane.

[0100] When the battery cell also includes a solid electrolyte membrane, the battery cell in the embodiments of this application is a battery cell of an all-solid-state battery. In the embodiments of this application, the specific selection of the solid electrolyte membrane is not limited; it can be any solid electrolyte membrane known in the art for use in all-solid-state batteries.

[0101] Secondary batteries The secondary battery of this application embodiment includes the battery cell of this application embodiment.

[0102] In some embodiments, the secondary battery includes all-solid-state batteries, etc.

[0103] <Electrical Appliances> The electrical device in this application includes the secondary battery in this application.

[0104] In some embodiments, the electrical device includes a vehicle, lighting device, electronic device, etc., and may be a vehicle.

[0105] The battery cell, secondary battery, and power device of the embodiments of this application all have at least the beneficial effects of the composite current collector, electrode, and electrode preparation method of the embodiments of this application.

[0106] The following non-limiting embodiments further illustrate certain features of the present technology.

[0107] I. Examples and Comparative Examples In the following examples and comparative examples, the lithium lanthanum zirconium oxide mentioned refers to lithium lanthanum zirconium oxide compounds ( (abbreviated as LLZO).

[0108] Example 1 (Composite current collector) like Figure 3-4 As shown ( Figure 3 , Figure 4 (This is only a schematic diagram of the structure of this embodiment and does not represent the actual product of this embodiment.) The composite current collector of this embodiment includes a current collector 1 and multiple solid electrolytes 2. The multiple solid electrolytes 2 are distributed in a lattice on the upper and lower surfaces of the current collector 1. The solid electrolytes 2 are lithium lanthanum zirconium oxide, and the solid electrolytes 2 are cylindrical in shape, with the bottom surface parallel to the upper surface of the current collector 1 (the upper and lower surfaces of the current collector 1 are set parallel to each other). The bottom diameter is 0.2 cm (i.e., a=0.2 cm), and the height is 100 μm (i.e., c=100 μm). The interval between two adjacent solid electrolytes 2 is 0.5 cm (i.e., b=0.5 cm). The current collector 1 is an aluminum foil with a thickness of 15 μm.

[0109] (Extreme film) The electrode in this embodiment is a positive electrode, including the composite current collector of this embodiment. Electrode material layers are provided on both the upper and lower surfaces of the current collector 1 in the composite current collector. Multiple solid electrolytes penetrate the electrode material layers (that is, multiple solid electrolytes located on the upper surface of the current collector 1 penetrate the electrode material layer on the upper surface of the current collector 1, and multiple solid electrolytes located on the lower surface of the current collector 1 penetrate the electrode material layer on the lower surface of the current collector 1). The surface of the electrode material layer away from the current collector 1 is flush with the surface of the multiple solid electrolytes away from the current collector 1. The mass content of the multiple solid electrolytes in the electrode is 10%. The electrode material layer is a positive electrode material layer, composed of the following components in parts by mass: NCM811 ( 90 parts, polytetrafluoroethylene (PTFE) 6 parts, conductive carbon black (Super-P) 4 parts.

[0110] The electrode preparation method of this embodiment includes: NCM811, PTFE, and Super-P were mixed uniformly at a mass ratio of 90:6:4 and placed in a high-shear mixer for fiberization to form a first mixture. Subsequently, the composite current collector and the first mixture were placed in a roller press, with the multiple solid electrolytes on the upper surface of current collector 1 in the composite current collector facing the first mixture, and subjected to hot rolling at a temperature of 90°C. During the hot rolling process, a large roll gap (300 μm) was initially used for rolling, followed by multiple progressively smaller rolls (the roll gap decreasing by 20% each time) until the height of the first mixture was flush with the multiple solid electrolytes on the upper surface of current collector 1 in the composite current collector, forming an electrode material layer on the upper surface of current collector 1 in the composite current collector. Then, an electrode material layer was formed on the lower surface of current collector 1 in the composite current collector in a similar manner.

[0111] (Secondary battery) The method for preparing the secondary battery in this embodiment includes the following steps: (1) Preparation of negative electrode sheet: The negative electrode active material artificial graphite, negative electrode binder, Super-P and The mixture is prepared by mixing the materials in a mass ratio of 69:4:2:25, and then placed in a high shear force mixer for fiberization to form a second mixture. The second mixture is then rolled to form a first negative electrode layer. The rolling temperature is 60℃ and the rolling time is 5min. The negative electrode current collector (copper foil with a thickness of 6μm) and the first negative electrode layer are stacked, hot-pressed, and cooled to form a composite negative electrode.

[0112] The negative electrode binder is a mixture of hydroxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR) in a mass ratio of 1:1.

[0113] (2) Preparation of solid electrolyte membrane: The halide solid electrolyte membrane is prepared by... Third halide solid electrolyte It is mixed with binder PTFE at a mass ratio of 62:35:3 and then pressed into a film with a thickness of 150 micrometers.

[0114] (3) Battery structure preparation: The electrode sheet (positive electrode sheet), the solid electrolyte membrane obtained in step (2), and the negative electrode sheet obtained in step (1) of this embodiment are stacked to obtain the battery structure.

[0115] (4) Hot pressing treatment: The battery structure obtained in step (3) is hot pressed to form an all-solid-state battery, wherein the hot pressing temperature is 130 ℃, the hot pressing time is 12 min, and the hot pressing pressure is 200 MPa.

[0116] Example 2 (Composite current collector) The composite current collector of this embodiment includes a current collector and multiple solid electrolytes; the multiple solid electrolytes are distributed in a lattice on the upper and lower surfaces of the current collector; the solid electrolytes are lithium-phosphorus-sulfur-chlorine compounds, and the solid electrolyte 2 is cylindrical in shape with its bottom surface parallel to the upper surface of the current collector (the upper and lower surfaces of the current collector are set parallel to each other), the bottom diameter is 0.2 cm (i.e., a=0.2 cm), and the height is 80 μm (i.e., c=80 μm); the interval between two adjacent solid electrolytes is 0.3 cm (i.e., b=0.3 cm); the current collector is a copper foil with a thickness of 6 μm.

[0117] (Extreme film) The electrode in this embodiment is a negative electrode, including the composite current collector of this embodiment. The composite current collector has an electrode material layer on both its upper and lower surfaces. Multiple solid electrolytes penetrate the electrode material layer (that is, multiple solid electrolytes located on the upper surface of the current collector penetrate the electrode material layer on the upper surface of the current collector, and multiple solid electrolytes located on the lower surface of the current collector penetrate the electrode material layer on the lower surface of the current collector). The surface of the electrode material layer away from the current collector is flush with the surface of the multiple solid electrolytes away from the current collector. The mass content of the multiple solid electrolytes in the electrode is 5%. The electrode material layer is a negative electrode material layer, which is composed of the following components in parts by mass: 88 parts of negative electrode active material artificial graphite, 8 parts of negative electrode binder, and 4 parts of conductive carbon black (Super-P). The negative electrode binder is a mixture of hydroxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR) in a mass ratio of 4:6.

[0118] The electrode preparation method of this embodiment includes: Artificial graphite (negative electrode active material), negative electrode binder, and Super-P were mixed uniformly at a mass ratio of 88:8:4 and placed in a high-shear mixer for fiberization to form a second mixture. Subsequently, the composite current collector and the second mixture were placed in a roller press, with the multiple solid electrolytes on the upper surface of the current collector in the composite current collector facing the second mixture, and subjected to hot rolling at a temperature of 60°C. Initially, rolling was performed with a large roll gap (300 μm), followed by multiple progressively smaller rolls (the roll gap decreasing by 20% each time) until the second mixture was flush with the height of the multiple solid electrolytes on the upper surface of the current collector in the composite current collector, forming an electrode material layer on the upper surface of the current collector in the composite current collector. Then, an electrode material layer was formed on the lower surface of the current collector in the composite current collector in a similar manner.

[0119] (Secondary battery) The method for preparing the secondary battery in this embodiment includes the following steps: (1) Preparation of positive electrode: NCM811 ( ), PTFE, Super-P and The mixture is prepared by mixing the materials in a mass ratio of 70:3:2:25, and then placed in a high-shear force mixer for fiberization to form a first mixture. The first mixture is then rolled to form a first positive electrode layer. The positive electrode current collector (aluminum foil with a thickness of 15μm) and the first positive electrode layer are stacked, hot-pressed, and cooled to form a composite positive electrode.

[0120] (2) Preparation of solid electrolyte membrane: The halide solid electrolyte membrane is prepared by... Third halide solid electrolyte It is mixed with binder PTFE at a mass ratio of 62:35:3 and then pressed into a film with a thickness of 150 micrometers.

[0121] (3) Battery structure preparation: The positive electrode obtained in step (1), the solid electrolyte membrane obtained in step (2), and the electrode (negative electrode) of this embodiment are stacked to obtain the battery structure.

[0122] (4) Hot pressing treatment: The battery structure obtained in step (3) is hot pressed to form an all-solid-state battery, wherein the hot pressing temperature is 130 ℃, the hot pressing time is 12 min, and the hot pressing pressure is 200 MPa.

[0123] Example 3 The secondary battery of this embodiment includes a positive electrode, a negative electrode, and a solid electrolyte membrane, wherein the positive electrode is the electrode from Example 1, and the negative electrode is the electrode from Example 2. The preparation method of this secondary battery includes the following steps: (1) Preparation of solid electrolyte membrane: The halide solid electrolyte membrane is prepared by... Third halide solid electrolyte It is mixed with binder PTFE at a mass ratio of 62:35:3 and then pressed into a film with a thickness of 150 micrometers.

[0124] (2) Battery structure preparation: The positive electrode, the solid electrolyte membrane obtained in step (1), and the negative electrode are stacked to obtain the battery structure.

[0125] (3) Hot pressing treatment: The battery structure obtained in step (2) is hot pressed to form an all-solid-state battery, wherein the hot pressing temperature is 130 ℃, the hot pressing time is 12 min, and the hot pressing pressure is 200 MPa.

[0126] Examples 4-14 are basically the same as Example 1, except that the selection of some substances and parameter values ​​in the composite current collector are different, as shown in Table 1.

[0127] Table 1. Selection of some materials and parameter values ​​for composite current collectors in Examples 1 and 4-14

[0128] Examples 15-22 are basically the same as Example 2, except that the selection of some substances and parameter values ​​in the composite current collector are different, as shown in Table 2.

[0129] Table 2. Selection of some materials and parameter values ​​for composite current collectors in Examples 2 and 15-22

[0130] Comparative Example 1 The method for preparing the secondary battery in this embodiment includes the following steps: (1) Preparation of positive electrode: NCM811 ( ), PTFE, Super-P and The mixture is prepared by mixing the materials in a mass ratio of 70:3:2:25, and then placed in a high-shear force mixer for fiberization to form a first mixture. The first mixture is then rolled to form a first positive electrode layer. The positive electrode current collector (aluminum foil with a thickness of 15μm) and the first positive electrode layer are stacked, hot-pressed, and cooled to form a composite positive electrode.

[0131] (2) Preparation of negative electrode sheet: The negative electrode active material artificial graphite, negative electrode binder, Super-P and The mixture is prepared by mixing the materials in a mass ratio of 69:4:2:25, and then placed in a high-shear force mixer for fiberization to form a second mixture. The second mixture is then rolled to form a first negative electrode layer. The rolling temperature is 60℃ and the rolling time is 5 minutes. The negative electrode current collector (copper foil with a thickness of 6μm) and the first negative electrode layer are stacked, hot-pressed, and cooled to form a composite negative electrode.

[0132] The negative electrode binder is a mixture of hydroxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR) in a mass ratio of 1:1.

[0133] (3) Preparation of solid electrolyte membrane: The halide solid electrolyte membrane is prepared by... Third halide solid electrolyte It is mixed with binder PTFE at a mass ratio of 62:35:3 and then pressed into a film with a thickness of 150 micrometers.

[0134] (4) Battery structure preparation: The positive electrode obtained in step (1), the solid electrolyte membrane obtained in step (3), and the negative electrode obtained in step (2) are stacked to obtain the battery structure.

[0135] (5) Hot pressing treatment: The battery structure obtained in step (4) is hot pressed to form an all-solid-state battery, wherein the hot pressing temperature is 130 ℃, the hot pressing time is 12 min, and the hot pressing pressure is 200 MPa.

[0136] Comparative Example 2 This embodiment is basically the same as embodiment 1, except that: In the composite current collector, the solid electrolyte 2 is a polyepoxide.

[0137] II. Performance Testing The positive electrode capacity utilization and 80% SOC cycle count of the secondary batteries in each embodiment and comparative example were tested separately. The test method was as follows: Positive electrode capacity utilization: The battery is charged and discharged at 0.33C at 25℃, and the battery discharge capacity is recorded. The positive electrode capacity utilization is calculated by dividing the battery discharge capacity by the mass of the positive electrode active material.

[0138] Cyclic performance test: The battery was charged and discharged at 25°C at a rate of 1C / 1C, and the number of cycles when the capacity retention rate was 80% was recorded.

[0139] The test results are shown in Table 3.

[0140] Table 3. Test results of secondary batteries in each embodiment and comparative example.

[0141] As can be seen from Table 3, the composite current collectors used in the various embodiments of this application can improve the solid-solid contact surface, enhance ion and electron transport capabilities, enable the cathode specific capacity to be effectively utilized, and reduce the problem of subsequent cycle decay caused by poor contact surface.

[0142] In summary, the composite current collector of this application uniformly and regularly arranges inorganic solid electrolytes in an array on the surface of the composite current collector of the electrode, forming a stable and continuous ion / electron conduction network through the regularly arranged inorganic solid electrolyte array. Compared with traditional electrodes doped with solid electrolytes, the electrode containing the composite current collector of this application can achieve rapid ion / electron transport, solve the problem of high impedance in the application of solid electrolytes in electrodes, and improve the electrochemical performance of the cell.

[0143] In this application, the terms "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., refer to a specific feature, structure, material, or characteristic described in connection with that embodiment or example, which is included in at least one embodiment or example of this application. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples.

[0144] Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of that feature. In the description of this application, "multiple" means at least two, such as two, three, etc., unless otherwise explicitly specified.

[0145] Although embodiments of this application have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting this application. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of this application.

Claims

1. A composite current collector, characterized in that, include: current collector; A plurality of solid electrolytes, wherein the array of the plurality of solid electrolytes is distributed in at least a portion of at least one surface of the current collector, wherein the solid electrolytes include inorganic solid electrolytes.

2. The composite current collector according to claim 1, characterized in that, The array distribution can be in the form of a dot matrix.

3. The composite current collector according to claim 1 or 2, characterized in that, The maximum dimension of the solid electrolyte in the first direction is a cm, where a satisfies: 0 < a ≤ 1; the first direction is the direction parallel to the surface of the current collector where the solid electrolyte is located.

4. The composite current collector according to claim 3, characterized in that, The condition 'a' satisfies: 0.05 < a ≤ 1.

5. The composite current collector according to any one of claims 1 to 4, characterized in that, The distance between two adjacent solid electrolytes located on the same surface of the current collector is b cm, where b satisfies: 0 < b ≤ 1.

6. The composite current collector according to claim 5, characterized in that, The condition b satisfies: 0.1 < b ≤ 1.

7. The composite current collector according to any one of claims 1 to 6, characterized in that, The maximum dimension of the solid electrolyte in the second direction is cμm, where c satisfies: 0<c≤200; the second direction is the direction perpendicular to the surface of the current collector where the solid electrolyte is located.

8. The composite current collector according to any one of claims 1 to 7, characterized in that, The inorganic solid electrolyte includes at least one of lithium aluminum titanium phosphate, lithium lanthanum zirconium oxide, lithium lanthanum titanate, aluminum-doped lithium lanthanum zirconium oxide, lithium germanium phosphorus sulfide, lithium phosphorus sulfide chloride, and lithium germanium aluminum phosphate. And / or, the current collector includes a positive current collector or a negative current collector.

9. An electrode sheet, characterized in that, It includes an electrode material layer and a composite current collector as described in any one of claims 1 to 8; the electrode material layer is disposed on the surface of the current collector on which the plurality of solid electrolytes are disposed.

10. The electrode sheet according to claim 9, characterized in that, The plurality of solid electrolytes penetrate the electrode material layer along the second direction; And / or, the mass content of the plurality of solid electrolytes in the electrode is d%, where d satisfies: 1≤d≤15; And / or, the outer surface of the electrode material layer in the second direction is flush with the outer surface of the solid electrolyte in the second direction; And / or, the electrode material layer includes a positive electrode active material or a negative electrode active material.

11. A method for preparing an electrode sheet as described in claim 9 or 10, characterized in that, include: The composite current collector is rolled with the material of the electrode material layer; During the rolling process, the roll gap is gradually reduced, and the current collector has at least one surface of the plurality of solid electrolytes facing the electrode material layer.

12. A single battery cell, characterized in that, It includes a positive electrode and a negative electrode, wherein the positive electrode and / or the negative electrode are the electrodes as described in claim 9 or 10; or, The positive electrode and / or the negative electrode are electrodes prepared by the preparation method as described in claim 11.

13. A secondary battery, characterized in that, Includes the battery cell as described in claim 12.

14. An electrical appliance, characterized in that, Includes the secondary battery as described in claim 13.